2023
DOI: 10.1021/acsanm.2c05454
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified CeO2-Octahedron-Supported Pt Nanoparticles as Ethylene Scavengers for Fruit Preservation

Abstract: Catalytic oxidation of ethylene associated with the preservation of fruits and vegetables (F&V) at low temperatures remains challenging. To address this issue, CeO2-octahedron-supported Pt catalysts were synthesized and modified by capacitively coupled plasma for efficient catalytic oxidation of C2H4. After the plasma treatment, CeO2 with rich oxygen vacancies was created, which acted as a support to facilitate the regulation of the size and dispersion of Pt nanoparticles. Compared with Pt/pristine CeO2, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Several metals such as Pt, Au, Ag and Ti have been used by researchers. 73 Moreover, Wei et al 95 found that Pt/CeO 2 –O showed the highest low temperature C 2 H 4 catalytic oxidation activity. In a separate study, it was noticed that CeO 2 -octahedron-supported Pt catalysts could be a better tool for catalytic oxidation of ethylene at low temperature.…”
Section: Management Strategies For Ethylenementioning
confidence: 99%
See 1 more Smart Citation
“…Several metals such as Pt, Au, Ag and Ti have been used by researchers. 73 Moreover, Wei et al 95 found that Pt/CeO 2 –O showed the highest low temperature C 2 H 4 catalytic oxidation activity. In a separate study, it was noticed that CeO 2 -octahedron-supported Pt catalysts could be a better tool for catalytic oxidation of ethylene at low temperature.…”
Section: Management Strategies For Ethylenementioning
confidence: 99%
“…In a separate study, it was noticed that CeO 2 -octahedron-supported Pt catalysts could be a better tool for catalytic oxidation of ethylene at low temperature. Wei et al 95 observed that a Pt/plasma-modified CeO 2 catalyst (Pt/CeO 2 -P) exhibited significantly higher catalytic reactivity of ethylene oxidation at low temperature compared to Pt/pristine CeO 2 .…”
Section: Management Strategies For Ethylenementioning
confidence: 99%
“…These interactions optimized the surface chemical states, promoted the formation of surface oxygen vacancies, activated the surface oxygen species, and improved the low-temperature reducibility. Wei et al 167 synthesized CeO 2 -octahedron-supported Pt catalysts and then modified them by capacitively coupled plasma to achieve efficient catalytic oxidation of C 2 H 4 . After the plasma treatment, CeO 2 with rich oxygen vacancies was created, which acted as the support to facilitate the regulation of the size and dispersion of Pt nanoparticles.…”
Section: Application Of Cerium-based Oxide Catalysts To Catalytic Eli...mentioning
confidence: 99%